Two Sides of the Same Coin?—Treatment of Chronic Asthma in Children and Adults - Chung, Li Ping; Paton, James Y. (Frontiers in Pediatrics, 2019)
Globally, asthma is one of the most common chronic conditions that affects individuals of all ages. When poorly controlled, it negatively impacts patient’s ability to enjoy life and work. At the population level, effective use of recommended strategies in children and adults can reduce symptom burden, improve quality of life and significantly reduce the risk of exacerbation, decline of lung function and asthma-related death. Inhaled corticosteroid as the initial maintenance therapy, ideally started within 2 years of symptom onset, is highly effective in both children and adults and across various degrees of asthma severity. If asthma is not controlled, the choice of subsequent add-on therapies differs between children and adults. Evidence supporting pharmacological approach to asthma management, especially for those with more severe disease, is more robust in adults compared to children. This is, in part, due to various challenges in diagnosis of asthma, recruitment for trials and lack of objective outcomes in children especially those in the preschool age group. Nevertheless, where evidence is emerging for younger children, it seems to mirror the observations in adults. Clinicians need to develop strategies to implement guideline-based recommendations while taking into consideration individual variations in asthma clinical phenotypes, pathophysiology and treatment responses at different ages.